Public figures rights to privacy: a legal perspectives / Aida Najihah Mhd Nazli, Siti Nur Farrah Abdul Rahman, Siti Syuhada Mohd Isa - Mhd Nazli, Aida Najihah; Abdul Rahman, Siti Nur Farrah; Mohd Isa, Siti Syuhada (2009)
This is a research project conducted to determine the right of privacy of public figures and how this right interacts with the freedom of the press especially in particular circumstances where a potential balancing of interests is not always an easy task. Basically, even though press claims that it was their duty as a press to collect information and publish it to public, but public figures or celebrities also are human beings where they have the right to do what they want in their daily life. The individual's right to privacy is a fundamental human right. They are still subjected to the protection of rights same as the ordinary people. As the Federal Constitution is the supreme law in the land, therefore it has been enumerated in Part II of the Federal Constitution, which stated that no person shall be deprived of his life or personal liberty saves in accordance with law. These provisions are applicable to everyone including public figures. By the virtue of Article 5 of the Federal Constitution that laid down the protection towards personal liberty while Article 8 outline that all people are subjected to equality before the law and being treated equally. Furthermore, it is recognized in key United Nations human rights documents such as the Universal Declaration of Human Rights 1948 particularly under Article 12 or the International Covenant on Civil and Political Rights 1966 by virtue of Article 17. Yes, every person is entitled to the same treatment and equal to subject before the law. Universal Declaration of Human Rights 1948 also gives protection towards human rights but does the law cover human rights as it is? Therefore, this research paper is to determine either the public figure deserve as well as celebrities deserve to have rights of privacy in their private life based on the legal perspective. Basically, in other countries the law of privacy has been amended as the authority never fail to ensure that all the citizens are protected. They do not take things for granted as every person in this world is subjected to an equal treatment and also deserve for privacy in private life. Therefore, it has to bear in mind that privacy law should be more effective and protect public figures' life too.